Latin American &Amp; Caribbean Petroleum Engineering Conference 2007
DOI: 10.2118/107837-ms
|View full text |Cite
|
Sign up to set email alerts
|

Heavy-Crude-Oil Upgrading With Transition Metals

Abstract: In this paper are discussed the effects of some metallic oxides used to upgrade the heavy crude oil properties. The underlying objective is to increase the mobility of the oil in the reservoir by reducing viscosity and improving the oil quality using alumina supported transition metals and liquid phase transition metals catalysts (derived from either acetylacetonate or alkylhexanoate compounds), both homogeneously mixed with heavy crude oil. This heavy crude oil upgrading is based on the decrement of the aspha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, they did not provide any data on the reduction of oil viscosity. The speculation was based on the observation that aluminium oxide is a good catalyst for upgrading heavy oil (Nares et al, 2007). Ogolo et al (2012) also found that some of the nanoparticles could reduce rock permeability or change wettability in the undesired direction and then decrease, instead of increase, oil recovery in many cases.…”
Section: Increase In the Viscosity Of Aqueous Solutionmentioning
confidence: 99%
“…However, they did not provide any data on the reduction of oil viscosity. The speculation was based on the observation that aluminium oxide is a good catalyst for upgrading heavy oil (Nares et al, 2007). Ogolo et al (2012) also found that some of the nanoparticles could reduce rock permeability or change wettability in the undesired direction and then decrease, instead of increase, oil recovery in many cases.…”
Section: Increase In the Viscosity Of Aqueous Solutionmentioning
confidence: 99%
“…SiO 2 is basically known as an IFT and θ depressant. , Using other metal NPs can also be a good option in EOR. For example, the effects of some metal particles, such as iron oxide (Fe 2 O 3 ), nickel oxide (Ni 2 O 3 ), and aluminum oxide (Al 2 O 3 ), as catalyst and support catalyst on changing the rheology of oil at high temperatures were determined within reactors. The results demonstrated that the viscosities of produced oils were reduced using metal particles through the aquathermolysis reactions. The presence of metal particles during aquathermolysis reactions can transfer the available hydrogen atoms to the free radicals, preventing polymeration and condensation reactions and preventing coke formation.…”
Section: Introductionmentioning
confidence: 99%
“…Steam channeling is an extreme form of thermal connectivity between thermal recovery wells. Although a heat viscosity reduction and recovery of crude oil in a cyclic steam stimulation (CSS) process mainly occur near wellbores, injection, and production replacement exists between multiple wells and multiple cycles, and serious steam channeling between wells is also easy to occur [19][20][21][22].…”
Section: Problems In Thermal Recovery For Heavy Oilmentioning
confidence: 99%